A brief measure of the triarchic model of psychopathy among community youths: psychometrics and measurement invariance. Issue 10 (26th November 2019) - Pechorro, Pedro; DeLisi, Matt; Ray, James V.; Alberto, Isabel; Simões, Mário R.
ABSTRACT: The development and validation of empirically sound measures that operationalize the Triarchic model of psychopathy among youth is currently in the nascent stage. The present study aimed to examine the psychometric properties of a brief refined measure of the Triarchic model of psychopathy based on the Youth Psychopathic Traits Inventory (YPI-Tri-S) among a mixed-gender school sample of 782 youth ( M  = 15.87 years, SD  = 1.72) from Portugal. Confirmatory factor analysis offered support for the theoretically expected three-factor structure. Cross-gender measurement invariance using the present sample and cross-sample measurement invariance of the YPI-Tri-S using a previously collected forensic sample of institutionalized males was established. The YPI-Tri-S showed adequate psychometric properties in terms of discriminant validity, convergent validity, concurrent criterion-related validity, known-groups validity, and internal consistency. Findings indicate that YPI-Tri-S is a valuable brief and psychometrically reliable and valid self-report measure of the Triarchic model of psychopathy for use in diverse samples of youth.